2010
DOI: 10.1016/j.fuproc.2009.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heating processes involving carbon materials

Abstract: Carbon materials are, in general, very good absorbents of microwaves, i.e., they are easily heated by microwave radiation. This characteristic allows them to be transformed by microwave heating, giving rise to new carbons with tailored properties, to be used as microwave receptors, in order to heat other materials indirectly, or to act as a catalyst and microwave receptor in different heterogeneous reactions. In recent years, the number of processes that combine the use of carbons and microwave heating instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
448
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 933 publications
(470 citation statements)
references
References 91 publications
6
448
0
16
Order By: Relevance
“…Results obtained can be explained by two processes that most probably take place during m/w heating. First one is the formation of local microplasma spots on graphite during irradiation that may result in the evaporation of liquid medium which assist in graphite exfoliation [37,41]. Second one is the exfoliation of graphite by m/w induced oscillation of polar groups of NaCMC which partially intercalate between sheets of graphite during sonication [48].…”
Section: Exfoliation Of Graphite To Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained can be explained by two processes that most probably take place during m/w heating. First one is the formation of local microplasma spots on graphite during irradiation that may result in the evaporation of liquid medium which assist in graphite exfoliation [37,41]. Second one is the exfoliation of graphite by m/w induced oscillation of polar groups of NaCMC which partially intercalate between sheets of graphite during sonication [48].…”
Section: Exfoliation Of Graphite To Graphenementioning
confidence: 99%
“…From our point of view an increase in the yield and speed of exfoliation can be achieved by using microwave (m/w) heating in addition to ultrasonication since graphene synthesis was reported to be facilitated by m/w heating [37][38][39][40] which was applied either for exfoliation of graphite directly [37][38][39] or for graphite oxide [40]. During m/w irradiation delocalized electrons of graphite can leave the material leading to the ionization of surrounding atmosphere and formation of microplasma spots where the temperature is considerably higher than overall temperature of the system [41] resulting in evaporation of liquid medium. Janowska et al [37] suggested that water vapors and decomposition products of intercalating compounds significantly increase pressure which we think can give rise to the exfoliation of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…There are several benefits of microwave heating in addition to volumetric heating [20], [21]. Selective material heating is a unique advantage of this technology that targets the specific material.…”
Section: Microwave and Conventional Heatingmentioning
confidence: 99%
“…Microwave energy has attracted increasing interest among the scientific community since the late eighties as an alternative method of heating [1,2]. A good indicator of this interest is the evolution in the number of scientific publications in the last thirty years (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in scientific efforts to develop microwave heating can be attributed to the several advantages that this technology offers over conventional heating technologies. These include: (i) non-contact heating; (ii) rapid heating; (iii) selective heating; (iv) a quick start/stop facility; (v) a high level of safety and automation; and (vi) heating from inside the body of the material (i.e., energy conversion instead of heat transfer) [1,3]. All of these advantages have promoted research into the application of microwave heating to a wide range of different processes including waste and biomass valorization [4], material synthesis [5,6], metallurgy and mineral processing [3,7], catalysis [8], organic synthesis [9], environmental technology [7,10], biomass extraction [11], etc.…”
Section: Introductionmentioning
confidence: 99%